(untitled) (Archaeologia Adriatica, 2022)
I have to explain the double name which this note appears with. Luciano Bosio left us in January 1997, without having the opportunity to publish the first part of an imposing work on a source he loved and frequented, and on which we had worked together. It was a sort of trilogy of the description of Italy as represented in the Tabula Peutingeriana (Roman Italy in the description of the Tabula Peutingeriana should have the title been); a trilogy formed by a volume on the morphological characters, a second one on the anthropic distribution (settlements of different consistency) and finally a third one on the road network, which should have been the most important in consideration of the purpose of the itinerarium pictum. As a moral inheritance of the commitment started with my master of Topography, I have resumed that work, starting from those morphological aspects that characterise our peninsula the most, in particular, in this case, the hydrography. In this note the Padus’s tributarys and Adige, Brenta, Livenza and Tagliamento will be considered specifically. Following the indications registered in the Tabula, these will be compared with the information which can be gathered from other sources, both literary and archaeological ones.